Tax instruments to support enterprises in the SME sector using the example of the communes of Lublin and Mazovia provinces - Żołądkiewicz-Kuzioła, Agnieszka (Podatkowe instrumenty wspierania przedsiębiorstw sektora MŚP na przykładzie gmin województwa lubelskiego i mazowieckiego, 2019)
The purpose of the paper is to assess the use of tax instruments by communes of the Lublin and Mazowia provinces as instruments to support enterprises in the SME sector, as well as the presentation of the opinions of micro, small and medium enterprises on the given instruments. For the purposes of the work, a description of tax instruments was made in terms of supporting enterprises. The article uses studies of the literature and the analysis of legal acts. The paper is based on the results of the author’s two studies, i.e. a survey conducted among all the communes in Poland and a focused group interview with representatives of private enterprises in the SME sector As a result of the research, it was found that communes largely use tax instruments to support enterprises. On the other hand, enterprises from the SME sector are willing to use these instruments owing to the improvement of their enterprise’s financial standing
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 117-126
Keywords: commune; SME sector; tax instruments; support for enterprises; local taxes and fees; gmina; sektor małych i średnich przedsiębiorstw; instrumenty podatkowe; wspieranie przedsiębiorstw; podatki i opłaty lokalne